Sustainability of Programming Education Through CDIO-Oriented Practice: An Empirical Study on Syntax-Level Structural Visualization for Functional Programming Languages - Lai, Chien-Hung; Ho, Liang-Chieh; Liao, Zi-Yi (Sustainability, 2025)
This study integrates the 2017 United Nations ESD framework and UNESCO’s ESD priorities with the Sustainable Development Goal (SDG) of “quality education” and the CDIO (Conceive, Design, Implement, Operate) framework to propose an innovative programming teaching model. A central component is an automatic architecture diagram generation system that visualizes program code structures in real-time, reducing cognitive load and enhancing comprehension of abstract programming concepts such as recursion and data structures. Students complete a project-based assignment—developing a Scheme interpreter—to simulate real-world software development. This model emphasizes system thinking, modular design, and problem solving, aligning with CDIO’s structured learning progression. The experimental results show that students using the system significantly outperformed the control group in their final project scores, demonstrating improved practical programming ability. While cognitive load remained stable, learning motivation decreased slightly, indicating the need for additional affective design support. The findings confirm that the integration of visual learning tools and project-based pedagogy under the CDIO framework supports the development of critical competencies for sustainable development. This approach offers a transformative step forward in programming education, cultivating learners who are capable, innovative, and ready to meaningfully contribute to global sustainability.